Application of ddPCR in detection of the status and abundance of EGFR T790M mutation in the plasma samples of non-small cell lung cancer patients - Zhang, Hui; Hu, Yi; Wang, Yan; Song, Xia; Hu, Ying; Ma, Li; Yang, Xinjie; Li, Kun; Qin, Na; Wang, Jinghui; Lv, Jialin; Li, Xi; et al. (Frontiers in Oncology, 2023)
The third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), such as osimertinib, designed for targeting the acquired drug resistant mutation of EGFR T790M, was approved as the first-line therapy for advanced EGFR-mutated NSCLC. Thus, detection of the EGFR T790M mutation for NSCLC is of crucial. However, the tissue samples are often difficult to obtain, especially in patients at advanced stages. This study assessed the performances of ddPCR and NGS in detecting EGFR T790M status and abundance in the plasma ctDNA samples of patients with NSCLC. Also, we explored the association between T790M status and abundance and the response to third-generation EGFR-TKIs. A total of 201 plasma samples with matched tissues, 821 plasma samples and 56 patients received third-generation EGFR-TKIs with response evaluation were included in this study. The results showed that the sensitivity and specificity of EGFR T790M mutation status detected by ddPCR in plasma samples were 81.82% and 91.85% as compared with the tissue samples, with a consistency coefficient of 0.740. Among the 821 plasma samples, the positive rates of EGFR T790M detected by ddPCR and NGS were 34.2% (281/821) and 22.5% (185/821), respectively. With NGS results as a reference, the sensitivity and specificity of ddPCR were 100% and 84.91%, and the consistency coefficient of the two methods was 0.717. In addition, we found that higher EGFR T790M abundance was linked to higher treatment response rate to the third-generation EGFR-TKIs regardless of the classification of median value of 0.43% (P = 0.016) or average value of 3.16% (P = 0.010). Taken together, this study revealed that ddPCR is an alternatively potent method for the detection of EGFR T790M in the plasma samples of NSCLC patients.